2022
DOI: 10.1038/s41392-022-00873-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic characterization of genome-wide abnormal DNA methylation reveals diagnostic and prognostic markers for esophageal squamous-cell carcinoma

Abstract: This study investigates aberrant DNA methylations as potential diagnosis and prognosis markers for esophageal squamous-cell carcinoma (ESCC), which if diagnosed at advanced stages has <30% five-year survival rate. Comparing genome-wide methylation sites of 91 ESCC and matched adjacent normal tissues, we identified 35,577 differentially methylated CpG sites (DMCs) and characterized their distribution patterns. Integrating whole-genome DNA and RNA-sequencing data of the same samples, we found multiple dysregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 78 publications
2
19
0
Order By: Relevance
“…Although hypermethylation events of the two genes were rarely reported in ESCC by previous studies, they have been extensively studied in other cancer types, especially in breast cancer [39,40]. Interestingly, in a recently published study, researchers have investigated the potential of HOXC10 as a diagnostic marker for ESCC [41]. Using the WGBS technology, they identified the hypermethylated HOXC10 in their cohort, which is consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 87%
“…Although hypermethylation events of the two genes were rarely reported in ESCC by previous studies, they have been extensively studied in other cancer types, especially in breast cancer [39,40]. Interestingly, in a recently published study, researchers have investigated the potential of HOXC10 as a diagnostic marker for ESCC [41]. Using the WGBS technology, they identified the hypermethylated HOXC10 in their cohort, which is consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 87%
“…Although hypermethylation events of the two genes are rarely reported in ESCC by previous studies, they have been extensively studied in other cancer types, especially in breast cancer [ 40 , 41 ]. Interestingly, in a recently published study, researchers have investigated the potential of HOXC10 as a diagnostic marker for ESCC [ 42 ]. Using the WGBS technology, they identified the hypermethylated HOXC10 in their cohort, which is consistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the DNA methylation that occurs here is highly correlated with the carcinogenesis of esophageal cancer. Specifically, during the carcinogenesis of esophageal cancer, altered DNA methylation status in CpG islands can lead to increased chromosomal rotation and silencing and loss of expression of oncogenes, leading to tumour growth ( Xi et al, 2022 ). A variety of related gene methylations have been examined in esophageal cancer, such as p16, E-cadherin, DNMT1 and MTHFR.…”
Section: Dna Methylation and Esophageal Cancermentioning
confidence: 99%